Heterópteros aquáticos como hospedeiros de Temnocephala Blanchard (Platyhelminthes: Temnocephalidae) em Minas Gerais, Brasil. (Lundiana: International Journal of Biodiversity, 2002)
Adults, immatures and eggs of Temnocephala decarloi Moretto and T. lanei Pereira & Cuocolo associated with Naucoridae, Nepidae and Belostomatidae species were recorded. The presence of Temnocephala associated with Heteroptera species is first reported for Brazil. It is suggestive that this association is relevant for Temnocephalidae dispersion and population maintenance owing to the morphology and behaviour of these insects and the oligotrophic state of the sampled localities.